PENGARUH KOORDINASI PERUM LPPNPI UNIT PELAYANAN NAVIGASI PENERBANGAN DENGAN STATION METEOROLOGI TERHADAP PELAYANAN NAVIGASI PENERBANGAN DI BANDAR UDARA YUVAI SEMARING LONG BAWAN - Dhiemas Darma Hidayah; Dewi Ratnasari; Siska Wijayanti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In providing air traffic navigation services, it cannot be separated from coordination with related units, one of which is coordination with the Meteorological Station. This coordination aims to provide weather information from the Meteorological Station, then the Flight Navigation Service Unit will convey it to the Pilot for take-off, landing, and en-route purposes. The research studied in this final project is how the effect of effective coordination between the Aviation Navigation Service Unit and the Meteorological Station on the efficiency of air traffic navigation services. (Y) is a flight navigation service at Yuvai Semaring Long Bawan Airport. The research method used is using a questionnaire, observation, documentation. Data analysis methods used are quantitative methods and data processing using a Likert scale. From the results of the research that the authors have done, the authors conclude that there is an important effect of coordination between the Aviation Navigation Service Unit and the Meteorological Station at Yuvai Semaring Long Bawan Airport. Coordination between the Aviation Navigation Service Unit and the Meteorological Station can run efficiently, infrastructure and communication facilities are updated in LOCA.